Operational decision-making in high-hazard organizations drawing a line in the sand - Hayes, Jan. (Burlington, Vt. : Ashgate Pub. Co., 2013)
"This book describes research on safety-related decision-making by operations supervisory personnel in three different high-hazard industries, and features a case study illustrating each: a chemical plant, a nuclear power station and an air-navigation service provider. The focus of this research is unique: those who supervise the frontline personnel and essentially provide the organizational link between senior management and minute-by-minute system operations"--Provided by publisher.
pt. A. Decision-making in three high reliability organizations -- pt. B. Acting both as employees and as professionals.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Supervisors, Industrial -- Decision making; Industrial safety -- Decision making; Industrial safety -- Risk assessment; Electronic books